Characterization of Potential Intoxications with Medicines in a Regional Setting - Tânia Nascimento; Teresa Santos; Fátima Rato; Ana Luísa De Sousa-Coelho (MDPI AG, 2023)
The Portuguese Poison Information Center (from Portuguese-CIAV) is a call center that offers medical assistance in case of possible intoxication with any kind of product, including medicines. This center´s main goal is to inform and guide the general public and health professionals. This work aimed to analyze and compare data corresponding to the telephone calls from the Algarve region (South of Portugal), received by CIAV during 2019 and 2020, regarding potential intoxications with medicines. To this end, data provided by CIAV on possible cases of medication intoxication in the Algarve region were collected, including the number of calls received, the place of origin of the call, the age group and sex of the intoxicated individual, the route of exposure to the drug, the circumstances of contact with the substance, the existence of symptoms, and the drug or drugs involved in the potential intoxication. The results showed that the number of cases slightly decreased in 2020 (n = 1261) compared with 2019 (n = 1340), with a high number of cases of intoxication in children between one and four years old in both years (21.2%; n = 152 in 2019; 16.4%; n = 115 in 2020). The drugs belonging to the locomotor system group (paracetamol and ibuprofen) were the main drugs involved, followed by the central nervous system pharmacotherapeutic group, namely benzodiazepines (diazepam and alprazolam). Paracetamol was the main drug responsible for the calls to CIAV (n = 71 in 2019; n = 63 in 2020), while for the remaining drugs there were fluctuations in their positions between both years. In some cases, this swinging may be explained by the possible changes in therapy due to potential interactions with drugs used for the treatment of symptoms of COVID-19 or perhaps related to misleading information released by the media about the use of some drugs, such as ibuprofen, during lockdown periods. Although there has been a decrease in calls to report possible drug intoxication in the Algarve region, the profile of calls was very similar. Paracetamol was the drug with the highest number of reported cases and the group of psychotropic drugs showed the largest increase between 2019 and 2020.